Konsep Karakter Pluralis dalam Al-Qur’an dan Internalisasinya dalam Dunia Pendidikan - Aminah (Jurnal Studi Al-Qur'an, 2021)
This article aims to explore the concept of pluralist character in the Quran and its internalization in the world of education. The method in this research uses a qualitative approach in the form of literature study to explore the concept of the Quran related to the Pluralist character. Also through observations, questionnaires and interviews to explore about its implementation at SD Kharisma Bangsa. Research findings show that the Quran directs Muslims to understand that diversity is a necessity; therefore it needs efforts to be able to respect each other among the existing differences; also able to be fair when working together. Internalization of Character Education at SD Kharisma Bangsa is carried out through SEL learning and also supported by exemplary and habituation.